Equilibrium Earnings Management, Incentive Contracts, and Accounting Standards* - LIANG, PIERRE JINGHONG (Contemporary Accounting Research, 2004)
Abstract In this paper, we model earnings management as a consequence of the interaction among self‐interested economic agents ‐ namely, the managers, the shareholders, and the regulators. In our model, a manager controls a stochastic production technology and makes periodic accounting reports about his or her performance; an owner chooses a compensation contract to induce desirable managerial inputs and reporting choices by the manager; and a regulatory body selects and enforces accounting standards to achieve certain social objectives. We show that various economic trade‐offs give rise to endogenous earnings management. Specifically, the owner may reduce agency costs by designing a compensation contract that tolerates some earnings management because such a contract allocates the compensation risk more efficiently. The earnings‐management activity produces accounting reports that deviate from those prescribed by accounting standards. Given such reports, the valuation of the firm may be nonlinear and s‐shaped, thereby recognizing the manager's reporting incentives. We also explore policy implications, noting that (1) the regulator may find enforcing a zero‐tolerance policy ‐ no earnings management allowed ‐ economically undesirable; and (2) when selecting the optimal accounting standard, valuation concerns may conflict with stewardship concerns. We conclude that earnings management is better understood in a strategic context that involves various economic trade‐offs.